Modern methods of fixation of biological material for educational purposes - К. N. Krupin; A. A. Supil'nikov; P. A. Lopanchuk; E. A. Mishurinskaya; Ya. Frishons (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
To ensure the safety of the educational process, the world is constantly looking for new ways to fix autopsy material. The purpose of our work was to search for literature data on new preservative solutions used in modern conditions for the fixation of cadaveric biological material for educational purposes. To achieve this goal, a scientific search was conducted on the RSCI and PUBMED database over the past 5 years with additional study of article-by-article links. As a result of the literature review, it has been established that modern methods of fixation of autopsy material have been developed, including solutions both containing formaldehyde and without its use. The current trend is determined by reducing the amount of formaldehyde used in such solutions or removing it from tissues before the educational process. Modern conservation techniques have proven themselves on the good  side, allowing for the realism of biological  tissues,  but they are always more  expensive than the standard fixation technique using an aqueous formaldehyde solution due to the cost of the solution or equipment itself.